2022
DOI: 10.3389/fcell.2022.837430
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Physical and Pharmacological Therapy in Enhancing Bone Regeneration Formation During Distraction Osteogenesis

Abstract: Distraction osteogenesis (DO) is a kind of bone regeneration technology. The principle is to incise the cortical bone and apply continuous and stable distraction force to the fractured end of the cortical bone, thereby promoting the proliferation of osteoblastic cells in the tension microenvironment and stimulating new bone formation. However, the long consolidation course of DO presumably lead to several complications such as infection, fracture, scar formation, delayed union and malunion. Therefore, it is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 126 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…In addition, delivery systems with an ability to locally control over spatial distribution and sustained release of these drugs or biological agents also need to be investigated (Porter et al, 2009;Oliveira et al, 2021). Physician stimulation is a low cost and noninvasive therapy that can change cell microenvironment (Liu et al, 2022). However, due to the complexity of the interaction between physical agents and biological systems, a lot work is still needed to find out the specific mechanisms (Massari et al,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, delivery systems with an ability to locally control over spatial distribution and sustained release of these drugs or biological agents also need to be investigated (Porter et al, 2009;Oliveira et al, 2021). Physician stimulation is a low cost and noninvasive therapy that can change cell microenvironment (Liu et al, 2022). However, due to the complexity of the interaction between physical agents and biological systems, a lot work is still needed to find out the specific mechanisms (Massari et al,…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapies have been popular in bone repair yield for many years due to its safety, non-invasiveness, economic benefits, easy access and controllability (Liu et al, 2022). Previous studies have shown that various kinds of physical stimuli contribute to osteogenic differentiation of PDLSCs, including mechanical stimulation, ultrasound stimuli and light stimuli (Zhang et al, 2012;Zhang et al, 2016;Li et al, 2021;Liu et al, 2022). Zhang et al (2016) treated PDLSCs with static stress and found that exposing PDLSCs to hydraulic pressure enhanced their osteodifferentiation via regulating RANKL/OPG ratio by the Wnt/β-catenin pathway.…”
Section: Physical Stimulation and Scaffold Modification For Pdlscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The llizarov technique used in DO dates back to 1951 and is widely utilized nowadays to treat bone defects, limb unequal lengths, and deformities ( 4 , 5 ). However, DO requires regular monitoring of callus growth due to the long treatment time, possible skin scar, psychological and life burden, pain syndrome, joint stiffness, pin tract infection, and bone non-union ( 6 ). Among them, bone non-union is a serious clinical issue, which prolongs the treatment course and increases the difficulty in bone extension ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the DO-related complications include bone nonunion, new bone fracture, nail infection and relaxation, muscle contracture and joint stiffness, force line deviation, etc. [ 4 7 ]. Among them, the bone nonunion is a serious clinical issue that prolong the treatment period and increase the burden i n bone lengthening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%